Policy of Agricultural Mechanization and Food Security in Nigeria: Challenges and Prospects - Ntagu, Miracle Promise; Nyam, Victor; Promise, Chinecherem Victory (NIU Journal of Social Sciences; Vol 8 No 1 (2022): NIU Journal of Social Sciences, Vol. 8 No. 1, March 2022, 2022)
This paper examined agricultural mechanization as strategy for food security in Nigeria. The study adopted a descriptive method of analysis. Data for the study were obtained from secondary sources archival search. The main findings of the research are: There is a relationship between agricultural mechanization and food security in Nigeria. Effective agricultural mechanization facilitates heavy food production in Nigeria. Alleged lack of availability of agricultural mechanization is a threat to food security in Nigeria. Farmers' inability to use agricultural mechanization tools effectively affects food security in Nigeria. The study identified some challenges militating against agricultural mechanization in Nigeria. These challenges are affordability of mechanization, non-availability of mechanization, lack of famer skills and high tariff in machine spare part. The study found out that the rural people are mostly poor and hardly can buy a costly machine individually. Another problem is that a large proportion of rural farming populations are illiterate. This situation stands in the way of improving agricultural production and productivity as well as general levels of farm management. The study concluded with some strategies to enhance agricultural mechanization for food security in Nigeria. The strategies are availability of finance and loans to farmers, capacity building of farmers. Others are development of local organization and the creation of enabling business environment. The study recommended that government should encourage and promote local design and manufacture of farm implements and equipment at low cost. Programmes and policies of the government especially agricultural mechanization and policy on tractorization should be given necessary funding so as to ensure food security.